Student or teacher? Its relevance on classroom motivational climate, motivation performance - Leal-Soto, Francisco (2023)
Main objective was to determine the effects of motivational configuration (CM) of the teacher and the student in group and individual levels, on classroom motivational climate (CMC), attributed motivation and satisfaction with the teacher (MASP) and estimated performance (RE). The data of 1,022 secondary students and 50 Bolivian teachers were analyzed using multilevel structural equation modeling. The CM of students and teachers was explained by motivational school climate, expectations of self-efficacy, goal orientation and beliefs about learning, knowledge and authority. The CM of the teacher had no impact on CMC, MASP and RE, but that of the student, especially the group level, which reflects common elements among the students of each class.